The impact of psoriasis on the lifequality: a cohort of 140 Moroccan patients - Awatef Kelati; Mariame Meziane; Mounir Jaafari; Fatima Zahra Mernissi (Our Dermatology Online, 2016)
Introduction: The alteration of the life quality in psoriasis is currently proved. Aim: To evaluate the particularity of this impact in Moroccan psoriatic population. Methods: It was a prospective cohort of 140 psoriatic patients who filled the 16-Skindex questionnary to evaluate this alteration of the life quality. Results: The life quality was significantly affected in patients having severe or old psoriasis and in young females, also it was related to the low Socioeconomic level and the living in rural areas, to the presence of psoriatic arthritis, to the scalp, the nails and mucosal involvement and to the use of systemic treatments. However, the emotional life, theimpact on daily activities and the sleep quality were not affected in our population. Conclusions: we had a low negative impact on the sleep quality and the emotional life which may be explained by the role of the family support in our society.